Compensation analysis of subsidence angle of supersonic low-altitude cruise target projectile launch - Guo, Hongli; Ren, Shaofeng; Yan, Huaiqiang; Zhao, Hongtao; Wei, Chunshuang; Gao, Yun (Journal of physics. Conference series, 2022)
Aiming at the launching process of the supersonic barrel-type spinning target projectile, and improving the control accuracy of the open-loop controlled target projectile, making the subsidence angle compensation can improve the accuracy of the launching process, and make the actual flight trajectory closer to the preset theoretical simulation trajectory. Studies have shown that the subsidence angle of the initial launch has a great impact on the actual flight trajectory. To achieve the same control effect, it must be adjusted to the corresponding control strategy. In this article, we provided the subsidence angle analysis method, which can truly reflect the change of the subsidence angle, and realize the precise control of the trajectory through effective compensation. CCS Concepts: Computing methodologies~Modeling and simulation~Model development and analysis~Model verification and validation